2018
DOI: 10.1136/jnnp-2017-317021
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal baclofen therapy versus conventional medical management for severe poststroke spasticity: results from a multicentre, randomised, controlled, open-label trial (SISTERS)

Abstract: BackgroundIntrathecal baclofen (ITB) is a treatment option for patients with severe poststroke spasticity (PSS) who have not reached their therapy goal with other interventions.Methods’Spasticity In Stroke–Randomised Study' (SISTERS) was a randomised, controlled, open-label, multicentre phase IV study to evaluate the efficacy and safety of ITB therapy versus conventional medical management (CMM) with oral antispastic medications for treatment of PSS. Patients with chronic stroke with spasticity in ≥2 extremiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 18 publications
1
31
0
2
Order By: Relevance
“…In line with current standards of care, both treatment arms received physiotherapy throughout the study. Results for the primary outcome, published previously, 19 showed a significant effect of treatment with ITB therapy over CMM for reduction of spasticity in the lower limb measured with the Ashworth Scale over 6-month follow-up. Furthermore, although the study was not powered for analysis of secondary outcomes, we observed a statistically significant treatment effect for ITB over CMM for spasticity reduction in the upper limb, indicating a substantial and broad effect of ITB therapy in PSS control.…”
mentioning
confidence: 58%
See 3 more Smart Citations
“…In line with current standards of care, both treatment arms received physiotherapy throughout the study. Results for the primary outcome, published previously, 19 showed a significant effect of treatment with ITB therapy over CMM for reduction of spasticity in the lower limb measured with the Ashworth Scale over 6-month follow-up. Furthermore, although the study was not powered for analysis of secondary outcomes, we observed a statistically significant treatment effect for ITB over CMM for spasticity reduction in the upper limb, indicating a substantial and broad effect of ITB therapy in PSS control.…”
mentioning
confidence: 58%
“…Twenty-five patients in the ITB arm were implanted with the device; of the 6 who were not implanted, 1 withdrew consent before the ITB test, 2 were lost to follow-up after the ITB test, and 3 were switched to CMM as previously described. 19 Twelve patients (7/31 [23%] and 5/29 [17%] in the ITB and CMM arms, respectively) discontinued prematurely and 48 patients completed follow-up at month 6 (24/31 [77%] in the ITB arm, including 22 implanted patients, versus 24/29 [83%] in the CMM arm). One ITB-implanted patient died after week 6 because of an unrelated cause (neither study drug nor study device).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…ITB therapy was originally evaluated for the treatment of severe spasticity of spinal origin (9,10), with indications expanded to include severe spasticity of cerebral origin, including cerebral palsy (11), brain injury (12), and stroke (13)(14)(15). Previous studies have demonstrated efficacy in spasticity of multiple origins, with long-term benefits (11,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%